Considerations and Perspectives on Interventions to Improve Social Cognition in Adolescents With ASD Without ID: Involving Parents in Social Skills Groups - Vuattoux, Delphine; Castiglia, Deborah; Chabane, Nadia (Frontiers in Psychiatry, 2021)
Improving social cognition and social skills is a challenge faced by individuals with Autism Spectrum Disorder without Intellectual Disability at any age. This process is particularly critical during late adolescence (15-18 years), a developmental phase generally characterized by rich social experiences that usually foster the development of friendships. Nevertheless, for youth with ASD, lingering difficulties in social cognition often hinder their ability to generate responses considered socially appropriated. These social deficits can contribute to isolation that has a detrimental effect on mental health. In adulthood, deficits of social skills are strongly associated with an overall lack of support, characterized by a failure to integrate into the labor market, a high unemployment rate, social isolation and a higher suicide rate. In clinical settings, social skills groups are well-established therapeutic means to improve social cognition and social skills. Nevertheless, these interventions vary greatly regarding their objectives, contents and duration. Moreover, few have been validated and replicated by research. Our aim is to bring certain perspectives to a type of intervention that are widely used in care settings. After reviewing its positive aspects for increasing social cognition, and its limitations, we will discuss strategies to facilitate the generalization of social skills in an ecological context. In particular, we will base our reflection on our clinical experience and on our current project to adapt the PEERS© model for adolescents into French. We will consider the current trend of involving parents as "social coaches" to generalize the social knowledge acquired in the social skills groups.